PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2018-2020 - Venolika, Nadila Putri Ayu; Sari, Lita Permata; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2022)
Property and Real Estate Company is one type of business that is growing rapidly in Indonesia. Property and Real Estate Company is one of the companies listed on the Indonesia Stock Exchange and is considered more productive and can provide wide-ranging effects so as to increase the added value of Property and Real Estate, increase workforce, generate foreign exchange sources, and contribute to taxes and customs. biggest. The purpose of this study was to determine the effect of Intellectual Capital on Company Value with Financial Distress as an intervening variable in Property and Real Estate companies listed on the IDX in 2018-2020. The population of this study is all property and real estate companies listed on the 2018-2020 period (IDX) as many as 73 companies. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation-Partial Least Square (PLS-SEM) method. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that intellectual capital has a negative but not significant effect on financial distress, intellectual capital has a significant negative effect on firm value, financial distress has a positive but not significant effect on firm value. The results of the indirect effect hypothesis test show that intellectual capital has a positive but not significant effect on firm value through financial distress.